From Information to Insight: How Digitalization and AI Reshape Management Accounting Systems Toward Strategic Value - Jeanne Adeline Savitri; Erine Tri Florensia; Luk Luk Fuadah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Digital transformation has reshaped Management Accounting Systems (MAS) from traditional reporting tools into strategic decision-support systems. This study employs a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines to examine Scopus Q1–Q4 journal articles published between 2016 and 2025 addressing digitalization, artificial intelligence (AI), and MAS. From an initial pool of 312 articles, 50 studies met the inclusion criteria and were synthesized. The findings indicate that digitalization enhances the quality of management accounting information through big data analytics, cloud-based ERP, business intelligence, and predictive analytics; the role of management accountants has shifted from administrative reporting toward strategic analysis; and technological readiness and data capabilities have emerged as new contingency factors determining the success of digital MAS implementation. These results confirm that digitalization generates strategic value when aligned with organizational information needs and strategy, while also highlighting opportunities for future research in developing-country contexts and the integration of MAS with sustainability-related issues.